Fishery Dynamics, Status, and Rebuilding Based on Catch-Only Data in Coastal Waters of China - Wang, Linlong; Lin, Li; Liu, Yang; Zhai, Lu; Ye, Shen (Frontiers in Marine Science, 2022)
China has become the largest contributor to marine fisheries in the world with its fishing fleets explosively increasing their fishing effort and resulting catch, but its fishery composition and sustainability have deteriorated. Limited information on fishery exploitation status encumbers effective resource management. In this study, a data-poor Monte Carlo method, the Catch-Maximum Sustainable Yield (CMSY) method, was used to estimate the historical exploited dynamics and current stock status of ten Chinese economic marine fish stocks, including Trichiurus lepturus, Larimichthys crocea, Larimichthys polyactis, Thamnaconus modestus, Scomberomorus niphonius, Ilisha elongate, Decapterus maruadsi, Scomber japonicus, Engraulis japonicus, and Clupea pallasii, which accounted for about 50% of total fish catches in the coastal waters of China and covered five functional groups (i.e., large, medium benthopelagic, large, medium, and small pelagic). Species L. crocea and L. polyactis had been subjected to overfishing since the 1950s. The others showed a decreasing trend in biomass along with the explosively increasing fishing efforts since the 1990s. Benthopelagic fish experienced overfishing pressure about a decade earlier than pelagic species. All the fish stocks investigated in this study were depleted (current biomass lower than the biomass capable of producing maximum sustainable yields, i.e., B < Bmsy) in 2019, and most species were still facing high-fishing pressure (current fishing mortality higher than the mortality capable of producing maximum sustainable yields, i.e., F > Fmsy). Also, a Schaefer model was used to assess stocks rebuilding status until 2030 under four exploitation scenarios, i.e., fishing mortality equals 0.5, 0.6, 0.8, or 0.95 times Fmsy. Most species stocks will likely recover to the Bmsy, which indicates that reduction of fishing pressure is probably the most effective way for fishery recovery.